Identify Smart Campus’ Features and Factors Which Affect Student Satisfaction in Using Its Services - Viktor Amos*; Nataniel Papalangi (Riwayat: Educational Journal of History and Humanities, 2023)
This study aims to identify the features of smart campus services on several campuses in the Makassar area as well as factors that affect student satisfaction using them. The unit of analysis includes all students at universities in Makassar. The research design uses qualitative design. Data was collected through a series of semi-structured interviews with seven (7) participants including students, lecturers, and technology infrastructure experts. Data was analyzed using thematic analysis with a cross-case analysis approach including open coding, axial coding and selective coding. On identifying factors that affect student satisfaction in accessing smart campus service features, five factors were found, namely: (1) factors of smart campus service types, some of the most popular are e-learning, digital payments, campus mobile applications, smart libraries, and campus internet, (2) the service display factors include user-friendly, service responsiveness, attractive interface, completeness of service, and interactivity, (3) administrative efficiency factors, with indicators of cost-effective, energy, time, lecture management, and up to date information, (4) environmental factors, indicators of providing new and supportive experiences, built technology infrastructure, quality of service, and convenience include data security and student privacy, (5) the caring factor of students needs  describes the ability of the service to care for student needs, including attention to social aspects of services, service centers, solutions and understanding student needs.